Polyurea carbon fibre composites - Lock, Daniel Wen Hao (Nanyang Technological University, 2020)
Polyurea displays good mechanical properties which make it suitable for absorbing large amounts of energy and sees use in blast resistant coatings for structures. Carbon fibres are known for their high strength and are commonly used as reinforcement phases in polymer matrix composites. Thus, the compositing of the two materials may potentially yield a product which is strong but light, both of which are traits that are desirable in armour applications. This project proposes a suitable method of fabrication for carbon fibre reinforced polyurea composites and also characterises its mechanical properties. The polyurea was prepared using diamine and isocyanate components, and the composite was formed using a hybrid hand layup and compression moulding method. Quasi-static tensile and compression tests were used to evaluate the mechanical properties of the composite. A split Hopkinson Pressure Bar was utilised to determine the response of the composite under high strain rate compression, and an optical microscope was used to examine for resin infiltration in the sample. Tensile test data shows yield strengths of samples with two layers of carbon fibre ranged between 87.9 and 114.71 MPa, averaging 100.97 MPa. Yield strength of samples with five layers ranged between 110.13 and 161.25 MPa, averaging 135.75 MPa. The average tensile Young’s modulus was 15.45 and 35.59 GPa for two and five carbon fibre layer samples, respectively. Quasi-static compression test results showed a 50% and 460% increase in Young’s modulus for samples with two and five layers of carbon fibre respectively. The composite also undergoes ductile failure at high strain rates in excess of 1600 s-1, achieving an average yield strength of 299.52 MPa and ranging from 267.3 to 351.1 MPa. These improvements in mechanical properties may possibly be exploited in personnel body armour or as spall liners for vehicle armour.